2016
DOI: 10.1111/ene.13234
|View full text |Cite
|
Sign up to set email alerts
|

Plasma D‐dimer levels and ischaemic lesions in multiple vascular regions can predict occult cancer in patients with cryptogenic stroke

Abstract: High plasma D-dimer levels and lesions in multiple vascular regions can be used to predict occult cancer in patients with cryptogenic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 28 publications
3
53
0
2
Order By: Relevance
“…Certain biological markers such as increased C-reactive protein (CRP), an unspecific acute phase reactant, and elevated fibrinogen and D-dimer, signaling a hypercoagulable state, have been suggested to have predictive values for underlying cancer [12, 13]. Radiological findings such as multiple acute cerebral infarcts (MACI) and specific cancer-related stroke patterns on diffusion weighted imaging (DWI) have also been suggested [13-16]. …”
Section: Introductionmentioning
confidence: 99%
“…Certain biological markers such as increased C-reactive protein (CRP), an unspecific acute phase reactant, and elevated fibrinogen and D-dimer, signaling a hypercoagulable state, have been suggested to have predictive values for underlying cancer [12, 13]. Radiological findings such as multiple acute cerebral infarcts (MACI) and specific cancer-related stroke patterns on diffusion weighted imaging (DWI) have also been suggested [13-16]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the multivariate analysis demonstrated that elevated levels of both FIB and D-dimer were independent risk factors for NHLAIS. However, elevated levels of FIB and D-dimer are reported to be biomarkers of the hypercoagulable state seen in patients with cancer [2,6], the pathogenesis of which has also been reported by several studies related to ischemic stroke [6,18,20,21]. Furthermore, Seok and colleagues [22] found an elevated D-dimer level linearly correlates to the frequency of microembolic signals in the internal carotid on transcranial Doppler ultrasound in cancer patients and patients with cryptogenic stroke.…”
Section: Resultsmentioning
confidence: 77%
“…16 The incidence of stroke as an initial manifestation of cancer varies in different studies and ranges from 0.4% to 10%. 6,17 Strokes are most commonly associated with lung cancer but have occurred in other cancers as well. 6,17 In patients with advanced adenocarcinoma, the risk of stroke recurrence is high.…”
Section: Discussionmentioning
confidence: 99%
“…6,17 Strokes are most commonly associated with lung cancer but have occurred in other cancers as well. 6,17 In patients with advanced adenocarcinoma, the risk of stroke recurrence is high. 18 Factors that increase stroke risk in patients with cancer are Trousseau's syndrome, non-bacterial thrombotic endocarditis, disseminated intravascular coagulation, coagulopathies, changes in blood viscosity, leukocytosis, radiotherapy, and anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation